The role of repetitive transcranial magnetic stimulation therapy in functional bowel disease - Li, Guangyao; Lv, Tingcong; Jin, Binghui; Fan, Zhe (Frontiers in Medicine, 2023)
This study investigates the effectiveness of repetitive transcranial magnetic stimulation (rTMS) as a biophysical therapy for alleviating symptoms of functional bowel disorder (FBD) and associated psychological symptoms by targeting the brain-gut axis.We conducted a comparative analysis involving 226 subjects, comprising the FBD group (n = 113) and a healthy control group (n = 113). Within the FBD group, participants were further divided into those who received rTMS therapy (FBD treatment group, n = 63) and those who did not (FBD control group, n = 50). The FBD treatment group was subcategorized based on the number of rTMS treatments received. We evaluated various factors, including gender, age, monthly household income, daily activity level, and sleep quality, as potential risk factors for FBD. Severity assessments of FBD and associated symptoms (constipation, anxiety, depression, and somatization disorders) were conducted using validated scales before and after treatment.Our findings revealed a higher incidence of FBD in women, with most cases emerging at age 50 or older. We identified lower monthly household income, reduced daily activity levels, and poorer sleep quality as factors associated with a higher likelihood of FBD. FBD patients exhibited higher scores for constipation, anxiety, depression, and somatization disorders compared to healthy controls. rTMS therapy was effective in reducing gastrointestinal symptoms, anxiety, depression, and somatization disorders among FBD patients. Notably, the extent of improvement was positively correlated with the number of rTMS sessions. No adverse effects were observed during the study.Our study underscores the efficacy of biophysical therapy, specifically repetitive transcranial magnetic stimulation, in mitigating FBD symptoms and associated psychological distress. The treatment's effectiveness is positively linked to the frequency of rTMS sessions.